HHV8‐unrelated primary effusion lymphoma in a patient with HBV‐related liver cirrhosis: A case successfully treated with rituximab and lenalidomide - Peng‐Jun Liao; Hui Yuan; Xiao‐Juan Wei (Clinical Case Reports, 2023)
Abstract Human herpesvirus type 8 (HHV‐8) unrelated primary effusion lymphoma (PEL) like lymphoma (PEL‐LL) is an exceedingly rare non‐Hodgkin lymphoma with no characteristic symptoms and consensus on the optimal treatment. This case report presents a 55‐year‐old man with prior HBV‐related Child‐Pugh B liver cirrhosis and developing activity‐related dyspnea. A moderate amount of pleural effusion was identified without tumor masses, and cytological studies confirmed a diagnosis of PEL‐LL. The patient received rituximab and lenalidomide, albeit with HBV infection, and is currently on maintenance therapy with resolving symptoms but without HBV reactivation. Hence, the R2 protocol (rituximab and lenalidomide) might be clinically effective and safe for PEL‐LL patients with HBV infection and Child‐Pugh B liver cirrhosis.